2018
DOI: 10.1177/2056305118803895
|View full text |Cite
|
Sign up to set email alerts
|

Domesticating Facebook: The Shift From Compulsive Connection to Personal Service Platform

Abstract: As one of the largest social media platforms, the meaning and role of Facebook is widely contested, where many argue that Facebook's cultural importance especially for younger generations, is declining. Popular thinking and common assumptions often position Facebook as a boring platform taken up by older generations. Yet, despite these claims, Facebook's user base continues to grow and it is still one of the most dominant global platforms in today's media ecology. This article provides insight into this appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…Polish HEI still lack a consistent strategy on how to utilise social media for communication. Similarly, HEIs need to adjust the channels of communicating with their stakeholders, whereas alumni and graduate students still can be researched with Facebook, younger generation of potential students are more likely to be present on other social media platforms (Sujon, Viney, & Toker-Turnalar, 2018). Our study revealed how much there is still to be done by HEIs in Poland.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Polish HEI still lack a consistent strategy on how to utilise social media for communication. Similarly, HEIs need to adjust the channels of communicating with their stakeholders, whereas alumni and graduate students still can be researched with Facebook, younger generation of potential students are more likely to be present on other social media platforms (Sujon, Viney, & Toker-Turnalar, 2018). Our study revealed how much there is still to be done by HEIs in Poland.…”
Section: Discussionmentioning
confidence: 88%
“…The value an organisation gains from utilising social media is inseparably determined by the specific platform taken advantage of. And therefore, when it comes to the scope and the purpose of the utilisation of social media, it is necessary to stress that Polish HEIs tend to consider Facebook a social media platform of the biggest significance -both now and in the future, despite its importance among students is diminishing (Sujon, Viney, & Toker-Turnalar, 2018). Snapchat is rather disregarded, despite the fact that it is becoming even more popular than Facebook among those who are soon going to be applying for admission to higher schools and universities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that trends in mobile communication are tied to different life stages (David-Barrett et al, 2016; Sujon et al, 2018). To make sense of the role that different stages play in our data set, we draw upon basic notions from the life course perspective.…”
Section: The Domestication Approachmentioning
confidence: 99%
“…I see these local daily circumstances as giving meaning to practices of allotting time for more extended phone calls and direct communication without other distractions. Given my respondents' middle-class background, this practice might also be seen as part of a wider shift that has been recently argued that Facebook is undergoing in its domestication process in middle-class user environments, a stage characterized by fewer emotional affordances and more mundane uses such as "scheduling," and "archiving" (Sujon, Viney, & Toker-Turnalar, 2018). This may be a way in which new media forms change the meaning of, or augment the affordances of, older media forms (Bolter & Grusin, 2000), or how multiple platforms used in parallel take on meaning with relation to one another as polymedia .…”
Section: Media Routines and Home Spacesmentioning
confidence: 99%